2006
DOI: 10.1016/j.jcp.2006.01.003
|View full text |Cite
|
Sign up to set email alerts
|

An efficient numerical quadrature for the calculation of the potential energy of wavefunctions expressed in the Daubechies wavelet basis

Abstract: Abstract.An efficient numerical quadrature is proposed for the approximate calculation of the potential energy in the context of pseudo potential electronic structure calculations with Daubechies wavelet and scaling function basis sets. Our quadrature is also applicable in the case of adaptive spatial resolution. Our theoretical error estimates are confirmed by numerical test calculations of the ground state energy and wave function of the harmonic oscillator in one dimension with and without adaptive resoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
0
36
0
Order By: Relevance
“…As described in Refs. 15,16,32 , from the expression of φ T α in a Daubechies wavelets basis set, the so-called "magic-filter" transformation can be used to define a real space representation of the basis functions, given in terms of one-dimensional interpolating scaling functions (ISF)…”
Section: E Reformatting Scheme For Roto-translationsmentioning
confidence: 99%
“…As described in Refs. 15,16,32 , from the expression of φ T α in a Daubechies wavelets basis set, the so-called "magic-filter" transformation can be used to define a real space representation of the basis functions, given in terms of one-dimensional interpolating scaling functions (ISF)…”
Section: E Reformatting Scheme For Roto-translationsmentioning
confidence: 99%
“…it has a rather low number of continuous derivatives. A. Neelov and S. Goedecker (22) have shown that one should not try to approximate a single matrix element as accurately as possible but that one should try instead to approximate directly the expectation value of the local potential. The reason for this strategy is that the wavefunction expressed in the Daubechy basis is smoother than a single Daubechies basis function.…”
Section: Treatment Of Local Potential Energymentioning
confidence: 99%
“…An integration scheme proposed in [40] has been employed successfully for computations involving smooth pseudopotentials in 3D with Daubechies wavelets, but is not suitable for our purposes due to its smoothness requirements on both potentials and wavefunctions.…”
Section: Evaluation Of Integralsmentioning
confidence: 99%